Group a Streptococcus remains viable inside fibrin clots and gains access to human plasminogen for subsequent fibrinolysis and dissemination - Henry M. Vu; Thomas E. Moran; Zhong Liang; Yun-Juan Bao; Paulina G. Carles; Jessica C. Keane; Madelyn G. Cerney; Caitlyn N. Dahnke; Ana L. Flores-Mireles; Victoria A. Ploplis; Francis J. Castellino; Shaun W. Lee (Microbiology Spectrum)
ABSTRACT Group A Streptococcus (GAS) is a major human pathogen that causes several invasive diseases including necrotizing fasciitis. The host coagulation cascade initiates fibrin clots to sequester bacteria to prevent dissemination into deeper tissues. GAS, especially skin-tropic bacterial strains, utilize specific virulence factors, plasminogen binding M-protein (PAM) and streptokinase (SK), to manipulate hemostasis and activate plasminogen to cause fibrinolysis and fibrin clot escape. A major unresolved question regards the temporal dynamics of how GAS enmeshed in a fibrin clot can access plasminogen for clot dissolution and eventual dissemination. Here, we reveal through live imaging studies that GAS trapped inside a fibrin clot can remain viable in a latent state, until access to plasminogen activates fibrinolysis and dissemination. RNA-sequencing (RNA-seq) analysis shows marked changes in the wild-type (WT)-GAS transcriptome from the time bacteria were enmeshed inside the clot (4 h) to when dissemination was initiated (8 h). To gain a more fully realized model of how GAS trapped in fibrin clots can disseminate in the blood system, we utilized a novel 3D endothelial microfluidic device to demonstrate that GAS is fully capable of fibrinolysis in an endothelial environment, revealing a major underappreciated route by which GAS may cause more invasive outcomes. Our findings reveal for the first time that GAS can engage a latent, growth-suspended phase whereby physical structures such as fibrin clots that immobilize an invading pathogen allow bacteria to remain viable until sufficient access to plasminogen allows it to initiate fibrinolysis and escape into surrounding blood system and tissues.IMPORTANCEGroup A Streptococcus (GAS) is a human-specific bacterial pathogen that causes infections ranging in severity from mild to severe infections that can often be fatal. To protect the host, the innate immune system creates fibrin clots to trap bacteria and prevent deeper spread. GAS produces several factors that can initiate the dissolution of these fibrin clots to spread to deeper tissues, but we lack specific understanding of the timing of these events. Our studies demonstrate for the first time that GAS can delay their escape from fibrin clots to gain access to deeper tissues during infection, suggesting a key strategy that GAS utilize to cause more invasive disease.